Strategies and Techniques for Data Compression in Wireless Sensor Networks - Wei Song (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The major challenge in designing wireless sensor networks (WSNs) is to resolve the limitation of energy and transmission capacity.  Data compression, as an effective solution, is attracted many attentions. In this paper, a survey is done on the strategies and techniques for data compression in WSNs. And the data compression schemes are divided into two classes: classical methods and the potential technique based on compressed sensing. The basic procedures of each method are further analyzed, and the existing problems are also highlighted. DOI: http://dx.doi.org/10.11591/telkomnika.v11i11.3507